Differential activation of dopaminergic systems in rat brain basal ganglia by morphine and methamphetamine. (13th May 2016) - Mori, T.; Iwase, Y.; Saeki, T.; Iwata, N.; Murata, A.; Masukawa, D.; Suzuki, T.
Highlights: Methamphetamine potently increases dopamine release from the striatum. Morphine produces an increase in dopamine from the nucleus accumbens, but not from the striatum. Morphine decreases GABA release in the ventral tegmental area, but not substantial nigra. Abstract: Typical abused drug-induced behavioral changes are ordinarily mediated by the mesolimbic dopaminergic system and even the phenotypes of behavior are different from each other. However, the mechanisms that underlie the behavioral changes induced by these abused drugs have not yet been elucidated. The present study was designed to investigate the mechanisms that underlie how abused drugs induce distinct behavioral changes using neurochemical as well as behavioral techniques in rats. Methamphetamine (2 mg/kg) more potently increased dopamine release from the striatum more than that from the nucleus accumbens. In contrast, the administration of morphine (10 mg/kg) produced a significant increase in the release of dopamine from the nucleus accumbens, but not the striatum, which is accompanied by a decrease in the release of GABA in the ventral tegmental area. These findings indicate that morphine and methamphetamine differentially regulate dopaminergic systems to produce behavioral changes, even though both drugs have abuse potential through activation of the mesolimbic dopaminergic system.